Improving Character Education through a Holistic Approach in Supporting the Achievement of SDGs 4 in Secondary Schools - Subasman, Iman; Maulidah, Idah; Nasyiruddin, Faat; Firmansyah, Bambang; Fauzi, Rifqi; Sulaiman, Sulaiman (Indonesian Journal of Advanced Research, 2025)
Holistic-based character education is an approach that emphasizes synergy between schools, families, and communities in shaping students' moral values. This study explores the effectiveness of a holistic approach in character education to support the achievement of SDGs 4 in secondary schools. The research used a mixed method, involving quantitative surveys and qualitative interviews with students, teachers, and parents in three high schools. The survey measures perceptions of the effectiveness of character education programs, while in-depth interviews explore implementation experiences and challenges. The data is analyzed with statistical and thematic approaches to provide comprehensive insights. The results show that the holistic-based character education program significantly improves students' moral values, such as honesty, responsibility, and the ability to work together. Parental involvement has been proven to strengthen family communication and support character education at home. Obstacles such as limited parental time indicate the need for flexibility in program implementation.